Qualitative news frame analysis: a methodology - Linström, Margaret; Marais, Willemien (Department of Communication Science, University of the Free State, 2012)
Framing theory has become increasingly popular in media analysis. The idea of framing is based largely upon the book by sociologist Erving Goffman (1974) titled Frame Analysis: An essay on the organization of experience. Goffman used the idea of frames to label “schemata of interpretation” that allow people “to locate, perceive, identify, and label” occurrences or events. With Robert Entman’s 1993 paper, frame analysis evolved into an important methodology. Since Goffman introduced the concept of frame analysis and Entman applied framing to the analysis of mass media, researchers have utilised it to understand how print and other media present information. Consequently for the last almost four decades, leading media scholars have applied the concept of framing to explain how the media structure their delivery of news, promoting certain interpretations of events by selecting certain facts. Frame analysis serves four main purposes within the context of media research – to define problems, to diagnose a course, to make value judgments, and to suggest remedies (Entman 1993: 52). In this article, the authors review the meaning of the concept of frame analysis, approaches to studying news framing, and qualitative news frame analysis. After defining news frames, we articulate a method for identifying news frames in print media.
Keywords: Framing theory; Media